Fosfomycin: Uses and potentialities in veterinary medicine - Pérez, Denisa Soledad (2014)
Fosfomycin (FOS) is a natural bactericidal broad-spectrum antibiotic which acts on proliferating bacteria by inhibiting cell wall and early murein/peptidoglycan synthesis. Bactericidal activity is evident against Gram positive and Gram negative bacteria and can also act synergistically with other antibiotics. Bacterial resistance to FOS may be natural or acquired. Other properties of this drug include inhibition of bacterial adhesion to epithelial cells, exopolysaccharide biofilm penetration, immunomodulatory effect, phagocytosis promotion and protection against the nephrotoxicity caused by other drugs. FOS has chemical characteristics not typically observed in organic phosphoric compounds and its molecular weight is almost the lowest of all the antimicrobials. It tends to form salts easily due to its acidic nature (disodium salt, for intravenous (IV), intramuscular (IM) and subcutaneous (SC) administration; calcium and trometamol salt: for oral (PO) administration). FOS has a very low protein binding (<0.5%) which, along with its low molecular weight and water solubility, contributes to its good diffusion into fluids (cerebrospinal fluid, aqueous and vitreous humor, interstitial fluid) and tissues (placenta, bone, muscle, liver, kidney and skin/fat). In all species, important differences in the bioavailability have been found after administration in relation to the various derivatives of FOS salts. Pharmacokinetic profiles have been described in humans, chickens, rabbits, cows, dogs, horses and weaning piglets. The low toxicity and potential efficacy of FOS are the main factors that contribute to its use in humans and animals. Thus, it has been used to treat a broad variety of bacterial infections in humans, such as localized peritonitis, brain abscesses, severe soft tissue infections, cystitis and other conditions. In veterinary medicine, FOS is used to treat infectious diseases of broiler chickens and pigs. In broilers, it is administered for the treatment of E. coli and Salmonella spp. infections. In piglets, the drug is prescribed to treat a wide variety of bacterial infections. FOS penetration is demonstrated in phagocytic, respiratory (HEP-2) and intestinal (IPEC-J2) cells. Although not widely used in animals, the drug has shown good results in human medicine. The potentialities of FOS suggest that this drug is a promising candidate for the treatment of infections in veterinary medicine. For these reasons, the aim of this work is to provide animal health practitioners with information on a drug that is not extensively recognized.